2008
DOI: 10.1016/j.freeradbiomed.2008.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Generation of nitroxyl by heme protein-mediated peroxidation of hydroxylamine but not N-hydroxy-L-arginine

Abstract: The chemical reactivity, toxicology and pharmacological responses to nitroxyl (HNO) are often distinctly different from those of nitric oxide (NO). The discovery that HNO donors may have pharmacological utility for treatment of cardiovascular disorders such as heart failure and ischemia reperfusion has led to increased speculation of potential endogenous pathways for HNO biosynthesis. Here, the ability of heme proteins to utilize H 2 O 2 to oxidize hydroxylamine (NH 2 OH) or N-hydroxy-L-arginine (NOHA) to HNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 67 publications
2
79
0
Order By: Relevance
“…Both NH 2 OH and hydroxyurea can be oxidized by peroxidases (33,69) [ Fig. 5 for NH 2 OH; a related two step process is suggested for hydroxyurea (69)].…”
Section: Pathways For Formation Of Endogenous Hnomentioning
confidence: 99%
See 2 more Smart Citations
“…Both NH 2 OH and hydroxyurea can be oxidized by peroxidases (33,69) [ Fig. 5 for NH 2 OH; a related two step process is suggested for hydroxyurea (69)].…”
Section: Pathways For Formation Of Endogenous Hnomentioning
confidence: 99%
“…Whether HNO will be capable of escaping the heme pocket seems to be protein dependent. A survey of heme proteins (33) showed that proteins such as Mb and myeloperoxidase, which have proximal histidine residues, can generate free HNO, as indicated by formation of sulfinamide. A lower affinity of the ferric heme for HNO may also correlate to a lower affinity for NO upon reductive nitrosylation.…”
Section: Pathways For Formation Of Endogenous Hnomentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent evidence suggests that HNO may also be active endogenously (22,33,35,38), and therefore likely to be of physiological significance. Indeed a number of potential biosynthetic pathways for HNO generation have been identified, including a) direct oxidation of the nitric oxide synthase (NOS) intermediates hydroxylamine (8) and Nhydroxy-L-arginine (19); b) nitrosothiol decomposition (44); c) direct reduction of NO by either mitochondrial cytochrome c, ubiquinol, and=or xanthine oxidase (20,36), and d) by NOS in the absence of the cofactor tetrahydrobiopterin (BH 4 ) (1).…”
Section: Introductionmentioning
confidence: 99%
“…But the significance of "free" HNO in nature is as yet uncertain (22). Although several biological pathways for HNO formation have been suggested, e.g., via nitrosothiol decomposition (23,24) or enzymatic malfunction (25)(26)(27), no true physiological role for endogenous HNO has been accepted. Following our previous characterization of the trapping of free HNO by various O 2 -binding globins (11), we hypothesized that HNO might similarly interact with O 2 -dependent oxygenases; we herein report the unprecedented substitution of HNO for O 2 in the activity of Mn-QDO, resulting in the incorporation of the nitroxyl-derived N atom into the product, which we denote as nitroxygenase activity.…”
mentioning
confidence: 99%